Determination of genetic variations among different Trichoderma isolates using RAPD marker in Bangladesh - Sagar, MSI; Meah, MB; Rahman, MM; Ghose, AK (Journal of the Bangladesh Agricultural University, 2011)
Some Trichoderma isolates were collected from different locations of Bangladesh for evaluating their bioefficiency by determining their genetic variations. PCR-based Random Amplified Polymorphic DNA (RAPD) Marker employing 3 decamer primers produced 29 scorable bands of which all (100%) were polymorphic. The co-efficient of gene differentiation (Gst) was 1.0000 reflecting the existence of high level of genetic diversity among the isolates. The Unweighted Pair Group Method of Arithmetic Means (UPGMA) dendrogram constructed from Nei’s (1972) genetic distance produced 2 main clusters (16 isolates in cluster 1 and 19 isolates in cluster 2). The result indicating their genetic diversity has opened new possibility of using the most efficient and more isolates of Trichoderma in the preparation of effective biopesticide. Keywords: Genetic diversity; Trichoderma; RAPD DOI: http://dx.doi.org/10.3329/jbau.v9i1.8738 JBAU 2011; 9(1): 9-20